Pengawet Alami Dari Berbagai Tanaman Indonesia Yang Diaplikasikan Pada Ikan Nila (Oreochromis niloticus): Studi Pustaka - Handarini, Kejora; Prajudanti, Adhania Andika; Rahmiati, Retnani; Kusyairi, Achmad (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed at identifying various plants in Indonesia that can be used as natural preservatives for Nile tilapia (Oreochromis niloticus), extraction methods and their application techniques. The method used in this literature study involved electronic searches in published databases such as PubMed, Wiley Online Library, and Google Scholar. Data acquisition was conducted by searching journals using specific keywords, focusing on journal publications from 2010 to 2025. The collected data were identified, analyzed, and evaluated, followed by compiling the analysis results to develop arguments and draw conclusions.The findings of this study indicate that (1) the plant parts used as natural preservatives include leaves, rhizomes, fruits, fruit peels, seeds, and stems, with leaves being the most frequently studied compared to roots, fruits, and seeds; (2) The active compounds with potential preservative properties in Indonesian plants include flavonoids, alkaloids, tannins, steroids, triterpenoids, saponins, glycosides, and essential oils; (3) Among extraction processes, maceration is the most commonly used technique for obtaining natural preservatives from plants; (4) The application methods used for these natural preservatives include soaking and coating techniques. Thus, it can be concluded that most of the examined plants exhibit excellent potential as natural preservatives for Nile tilapia (Oreochromis niloticus) based on chemical, microbiological, and organoleptic aspects.